EFFECT OF SUBCUTANEOUS ZERANOL IMPLANTS ON MEAT QUALITY OF AWASSI LAMBS AND CROSS-BRED KHALKHALI AND ABADEH GOAT KIDS - Al-doski, S. H.; Kak, H. F.; Khurshid, J. S.; Vriesekoop, F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This experiment was conducted to evaluate the effects zeranol implant on meat quality of Awassi lambs and cross-bred Khalkhali and Abadeh goat kids. Ten ram lambs (33.7 ± 0.5 kg and 4-month-old) and ten male goat kids (18.8 ± 0.7 kg and 4-month-old) were randomly assigned into two treatments (5 each treatment); C (control, 0 mg zeranol) and Z (24 mg zeranol implant) for each species. After 43 days experimental period. The animals were slaughtered, left for 24 hr post-mortem period and Biceps femoris muscle of each species were separated for measuring the proximal composition, TBARS values, cooking loss, drip loss and free fatty acids concentrations. Zeranol implants had significant (P